Improving cereal productivity through climate smart practices - Sareen, Sindhu (Woodhead Publishing, 2021)
Improving Cereal Productivity through Climate Smart Practices is based on the presentations of the 4th International Group Meeting on "Wheat productivity enhancement through climate smart practices," and moves beyond the presentations to provide additional depth and breadth on this important topic. Focused specifically on wheat, and with chapters contributed by globally renowned pioneers in the field of cereal science, the book helps readers understand climate change and its effects on different aspects of wheat production in different parts of the world. This book will be important for those in research and industry seeking to contribute to the effective feeding of the world's population.